The role of social capital in the innovative development of society - Gad, Salah; Bauer, Maira; Tyurina, Yuliya; Kolmykova, Marina (Opción, 2020)
The purpose of research is to conduct a survey among students to determine their attitude to social capital and its impact on the development of communities; identify the main problems that may be associated with social capital; develop recommendations that can help solve problems in this area via an empirical study based on a survey method. The results of the study demonstrated that students may not fully understand the very definition of social capital; however, they realize that it affects the development of the community. In conclusion, social capital plays an important role in the formation and development of communities